COMPUTER MODELING OF THERMOFLUID ANOMALY INFLUENCE ON THE STRESS-DEFORMATION STATE OF FAULT ZONES - SHEVCHUK, V.; LAVRENIUK, M.; SHEVCHUK, Vol. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
Сalculation geoinformatic module of the thermoelasticity and a phase transformation assessment during the granitization caused by thermo fluids flows has been developed. It influences on the stress-deformation state of the fault zones with a directional permeability.